2012
DOI: 10.1007/s00418-012-1038-9
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant metabolism and anti-oxidative capacity in hyperoxic neonatal rat lungs: effects of keratinocyte growth factor on gene expression in vivo

Abstract: Development of preterm infant lungs is frequently impaired resulting in bronchopulmoary dysplasia (BPD). BPD results from interruption of physiologic anabolic intrauterine conditions, the inflammatory basis and therapeutic consequences of premature delivery, including increased oxygen supply for air breathing. The latter requires surfactant, produced by alveolar type II (AT II) cells to lower surface tension at the pulmonary air:liquid interface. Its main components are specific phosphatidylcholine (PC) specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A recent report also showed that TrxR may help regulate redox balance, the survival of rheumatoid synoviocytes, and celluar responses to different cytotoxic drugs and protect damaged neurons from oxidative stress . TrxR mRNA expression in AEC II was also associated with exposure to hyperoxia . This finding further indicated that the cytoplasmic Trx system may play a key role in this mechanism.…”
Section: Trxr and Its Protein Targetsmentioning
confidence: 79%
See 1 more Smart Citation
“…A recent report also showed that TrxR may help regulate redox balance, the survival of rheumatoid synoviocytes, and celluar responses to different cytotoxic drugs and protect damaged neurons from oxidative stress . TrxR mRNA expression in AEC II was also associated with exposure to hyperoxia . This finding further indicated that the cytoplasmic Trx system may play a key role in this mechanism.…”
Section: Trxr and Its Protein Targetsmentioning
confidence: 79%
“…90 TrxR mRNA expression in AEC II was also associated with exposure to hyperoxia. 91 This finding further indicated that the cytoplasmic Trx system may play a key role in this mechanism.…”
Section: Trxr and Its Protein Targetsmentioning
confidence: 87%
“…Since normal alveolar oxygen pressures lead to pro-inflammatory effects, the presence of local antioxidants is necessary to negate such effects. Since the surfactant-stimulating recombinant human keratinocyte growth factor (rhKGF) has been proposed to assist in diminishing the injurious effects of hyperoxia on pulmonary epithelial cells, Koslowski et al (2013) performed experiments to investigate the use of rhKGF in improving expression parameters of lung maturity in newborn rats subjected to hyperoxia. In response to rhKGF treatment, they found the following results: (1) increased PCNA mRNA expression, indicating enhanced cell proliferation; (2) increased expression of three genes involved in oxygen radical protection (ATP-binding cassette protein A3, thioredoxin, and thioredoxin reductase); and (3) increased mRNA levels of acyl-coA:lysophosphatidylcholine acyltransferase I (catalyzes dipalmitoyl-PC synthesis) and adipose triglyceride lipase (supplies fatty acids for surfactant PC synthesis).…”
Section: Respiratory and Cardiovascular Systemsmentioning
confidence: 99%